Ibermedia as a collaborative space for film co-production policy? A stakeholder analysis on decision-making processes (Communication & Society, 2022)
Ibermedia is the most important institution in the Ibero-American audiovisual space. It was created as a result of a bottom-up project that aims to include stakeholders in policy-making. The paper investigates the participation of stakeholders in the Ibermedia decision-making in order to assess if it maintains its original cooperative character. We applied the salience theory to identify who and why is being taken into account by the organization. Our findings are based on a literature review, qualitative document analysis, and semi-structured expert interviews. The findings reveal that Ibermedia maintains its bottom-up proposal and the stakeholders can impact its policies. The interactions are marked by informal relations and affection. The stakeholders consider Ibermedia vital and are generally satisfied with its functioning, besides its low budget. The paper provides an overview of the internal functioning of Ibermedia, revealing the level of interaction with the stakeholders and contributes to add light in the lack of transparency.